Ohmic heating treatment - Vicente, A. A. (2012)
[Excerpt] Introduction: Thermal processing has most of the characteristics of an “ideal” food preservation method. However, in some foods the high thermotolerance of certain enzymes and microorganisms, their physical properties (e.g. high viscosity) or their components (e.g. solid fractions), require the application of extreme heat treatments that not only are energy intensive, but also will adversely affect the nutritional and organoleptic properties of foods. Therefore, more efficient alternatives to the inactivation of pathogenic and spoilage microorganisms are constantly sought by the food industry. Ohmic heating (OH) is an alternative thermal processing method where heat is generated directly inside the food, which plays the role of an electrical resistance (Fig. 27.1). OH can ensure the benefits of conventional thermal processing (food safety and preservation) while offering the potential for improvements in the preservation of vitamins and nutrients (Ruan et al., 2002). OH is alternatively called Joule heating, electroheating, resistance heating or direct resistance heating. The principal advantage of OH is the ability to heat materials rapidly and uniformly; thus overprocessing of foods can largely be prevented. In addition, the absence of a hot surface in direct contact with food reduces fouling problems and thermal damage to the product. Furthermore, there are clear signs of effective action of the electric field per se over microorganisms and enzymes, in addition to the effects of temperature, which clearly point at the possibility for shorter, less aggressive treatments. Therefore, by minimizing destruction of nutrients and flavor compounds, a high-quality product can be manufactured with even shorter operation times (Sastry and Barach, 2000). [...]